Cigarette Smoking Is Significantly Linked to Sexual Dissatisfaction in Chinese Heroin-Dependent Patients Receiving Methadone Maintenance Treatment - Zhong, Bao-Liang; Xu, Yan-Min; Xie, Wu-Xiang; Lu, Jin (Frontiers in Psychiatry, 2019)
Background: Cigarette smoking is associated with sexual dysfunction in the general population. Both smoking and sexual dysfunction are common in heroin-dependent patients (HDPs) receiving methadone maintenance treatment (MMT), but their association in MMT HDPs is rarely studied. This study examined the association between smoking and sexual dissatisfaction in Chinese HDPs receiving MMT. Methods: In total, 480 Chinese HDPs, who had sex with their regular or irregular sex partners within one month prior to the study, were included from three MMT clinics in Wuhan, China. Sexual dissatisfaction was assessed with one single question. Socio-demographic and clinical data and smoking characteristics were collected with a standardized questionnaire. Multiple binary logistic regression was used to analyze the association between smoking and sexual dissatisfaction, as well as the associations between levels of smoking and nicotine dependence and sexual dissatisfaction. Results: The prevalence of current smoking was 95.6% in HDPs receiving MMT. Rates of sexual dissatisfaction were higher in current smokers than non-smokers (32.9% vs. 14.3%) with a borderline significant P value of 0.074. After adjusting potential socio-demographic and clinical confounders, current smoking was significantly linked to sexual dissatisfaction (OR = 1.95, P = 0.026), and heavy smoking and severe nicotine dependence were significantly linked to sexual dissatisfaction (OR = 1.80, P = 0.025; OR = 3.27, P < 0.001). Conclusion: Smoking is significantly associated with sexual dysfunction in HDPs receiving MMT. It deserves further investigation as to whether quitting smoking can improve the sexual function of methadone-maintained patients.